1994
DOI: 10.1128/jcm.32.4.893-896.1994
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of PCR test for detection of Taylorella equigenitalis

Abstract: A PCR for the detection of Taylorella equigenitalis, the causative agent of contagious equine metritis, was developed and evaluated. A genus-specific primer-probe set was derived from the 16S ribosomal DNA sequences. The PCR was specific and amplified a 585-bp product from all 64 available T. equigenitalis isolates. This PCR product hybridized with a specific probe in a dot spot assay. A variety of microorganisms from the genital tracts of horses or with a close phylogenetic relationship to T. equigenitalis di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…The simplicity, clarity and rapidity of the PCR assay should be noted when considering the PCR as a good supplementary procedure for detection of T. equigenitalis. Bleumink-Pluym et al (1994) reported the development and application of a PCR capable of detecting 10-15 bacteria based on the sequence of the 16S rRNA gene which is present in multiple copies in the bacterial genome. Anzai et al (1999) developed and evaluated a PCR with species-specific primer sets derived from the DNA sequence of a cloned DNA fragment of T. equigenitalis that did not hybridise with the genome of taxonomically related species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplicity, clarity and rapidity of the PCR assay should be noted when considering the PCR as a good supplementary procedure for detection of T. equigenitalis. Bleumink-Pluym et al (1994) reported the development and application of a PCR capable of detecting 10-15 bacteria based on the sequence of the 16S rRNA gene which is present in multiple copies in the bacterial genome. Anzai et al (1999) developed and evaluated a PCR with species-specific primer sets derived from the DNA sequence of a cloned DNA fragment of T. equigenitalis that did not hybridise with the genome of taxonomically related species.…”
Section: Discussionmentioning
confidence: 99%
“…The suspensions were heated at 100°C for 15 mins and then centrifuged at 15,000 g for 2 mins. Five µl supernatant were used for PCR, which was performed according to 2 different protocols with different primer sets as described previously (Bleumink-Pluym et al 1994;Anzai et al 1999). The PCR products were electrophoresed in 2% agarose gel and visualised with ethidium bromide.…”
Section: Pcr: T Equigenitalis Culturementioning
confidence: 99%
“…3,1996 INVASION AND REPLICATION OF T. EQUIGENITALIS traits, probably encoded by separate genes. A clinical evaluation of a PCR demonstrates that T. equigenitalis is present in 35% of tested healthy horses (2). This means that a considerable number of horses carry Taylorella spp.…”
Section: Discussionmentioning
confidence: 99%
“…A few polymerase chain reaction (PCR)-based methods for detecting T . equigenitalis have been described [ 1 , 2 ]. However, it is difficult to use PCR-based methods in less well-equipped laboratories, because special equipment such as a thermal cycler is needed.…”
mentioning
confidence: 99%
“…Two PCR-based methods—namely PCR [ 2 ] and semi-nested PCR [ 1 ], were used to compare the analytical sensitivity for experimentally spiked samples. The PCR assay detects both T .…”
mentioning
confidence: 99%